UNIVERSITY GARUT and UIN BANDUNG COMMUNITY SERVICE TEAMS COLLABORATE to RAISE STUDENTS' AWARENESS of CHOOSING HEALTHY SNACKS WISELY - Lubis, Novriyanti; Wahyuningsih, Wahyuningsih; Belfa, Muhammad; Chandra, Mahesa Prana; Lindayani, Lindayani; Handayani, Niknik; Aulia, Naila Azqiatul; Anam, Khairul (Indonesian Journal of Community Empowerment (IJCE), 2025)
Snacking at school is a common practice among students. The availability of snacks in the school environment cannot guarantee that all snacks are healthy. This outreach activity was conducted to increase the knowledge and awareness of students at SDN 1 Kadungora, encouraging them to be wiser in choosing the snacks they consume. Data collection methods included a pre-test and post-test. The material was delivered in the form of a lecture accompanied by PowerPoint slides and printed brochures. The outreach results showed an increase in the percentage of students' understanding of the definition of healthy snacks before the outreach: 82.4% before the outreach and 92.8% after the outreach. For healthy drinks, there was a 10.4% increase in knowledge, and 100% of students understood examples of healthy drinks. This indicates that the outreach activity was successful in educating students.